PERLINDUNGAN DATA PRIBADI PASIEN TERHADAP SERANGAN CYBER CRIME - Arya Wirai Khalifatullah; Afifah Fitri Apsari; Anifatun Lutfiyah; Ervina Anisya Qoriah; Anisya Qoriah; Gesit Syaifrudin Zukhri; Muh. Rizal Rosyid Ridho (Sanskara Hukum dan HAM, 2022)
The right is the authority (legal entity) that a person has to obtain the rights obtained by the patient. The patient's right is to receive an explanation of hospital rules, medical services, or the patient's illness. Likewise, the hospital must also inform the patient about the patient's health problems or what the patient is suffering from smoothly, clearly, and definitely, without any distraction from the medical record, so we as the implementation of the hospital try as much as possible to protect the patient's personal data. for the suffering that has been experienced in the hospital, because in this era it is very dangerous to have news from outside about data breaches of patients on social media or this greatly affects the identity of patients and the hospital for spreading good names. Even though the Health Law does not clearly state it, the definition of a hospital can be concluded as a form of health service facility. As formulated in Article 1 point 7 that "Health service facility is a tool and/or place that is used to carry out health service efforts, both preventive, curative and rehabilitative carried out by the regional government and the community.